2014
DOI: 10.1007/s00239-014-9639-7
|View full text |Cite
|
Sign up to set email alerts
|

One origin for metallo-β-lactamase activity, or two? An investigation assessing a diverse set of reconstructed ancestral sequences based on a sample of phylogenetic trees

Abstract: Bacteria use metallo-β-lactamase enzymes to hydrolyse lactam rings found in many antibiotics, rendering them ineffective. Metallo-β-lactamase activity is thought to be polyphyletic, having arisen on more than one occasion within a single functionally diverse homologous superfamily. Since discovery of multiple origins of enzymatic activity conferring antibiotic resistance has broad implications for the continued clinical use of antibiotics, we test the hypothesis of polyphyly further; if lactamase function has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 91 publications
0
30
0
1
Order By: Relevance
“…Cross-validation was used to optimize the true positive rate to identify previously undescribed B1BL genes. For full-length genes, the method correctly classified all tested B1BL genes (an estimated true positive rate of 100%), while the false positive rate (FPR) was very low, even for closely related genes from the MBL superfamily [23] (an FPR of 0% for all tested gene groups within the MBL superfamily). For metagenomic data, using a fragment length of 100 nucleotides, the method showed a true positive rate of 89% and a FPR of 4% and 0% for the MBL superfamily and random genomic fragments, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-validation was used to optimize the true positive rate to identify previously undescribed B1BL genes. For full-length genes, the method correctly classified all tested B1BL genes (an estimated true positive rate of 100%), while the false positive rate (FPR) was very low, even for closely related genes from the MBL superfamily [23] (an FPR of 0% for all tested gene groups within the MBL superfamily). For metagenomic data, using a fragment length of 100 nucleotides, the method showed a true positive rate of 89% and a FPR of 4% and 0% for the MBL superfamily and random genomic fragments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, if these genes were to become mobilized and spread to pathogenic bacteria, they may constitute a threat to human health in the future [45]. Furthermore, the large increase in known chromosomal B1BL genes will enable more detailed phylogenetic studies of the B1 subclass of metallo-β-lactamases [23], an essential step to further elucidate the evolution and origins of mobile B1BL genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The giant virus mRNAs should be protected from such a degradation, which may be explained by the encapsidation of RNA transcripts into giant virions that was detected for some of these viruses 27 . Bioinformatic analyses suggested that the tupanvirus MBL fold protein may belong to the RNase Z group that was proposed to be one of the two main groups of the MBL superfamily with that encompassing MBLs 1 . RNase Z enzymes perform tRNA maturation by catalyzing the endoribonucleolytic removal of the 3’ extension of tRNA precursors that do not contain a chromosomally-encoded CCA determinant 2830 .…”
Section: Discussionmentioning
confidence: 99%
“…The metallo-beta-lactamase (MBL) superfamily encompasses a large set of enzymes, including MBL and ribonuclease (RNase) Z enzymes 1 . These enzymes are pleitropic proteins that can hydrolyze a wide range of substrates, among which beta-lactams, and DNA or RNA 2,3 .…”
Section: Introductionmentioning
confidence: 99%